Plant Materials for the Production of Functional Foods for Weight Management and Obesity Prevention - Stabnikova, Olena; Paredes-López, Octavio (Current Nutrition & Food Science, 2024)
Obesity is a serious problem in the modern world and is considered a risk factor in the development of many human diseases. Consumption of low-calorie, low-fat diets, together with increased physical activity and a healthy lifestyle, contribute a lot to the fight against obesity. Meanwhile, functional foods with a reduced calorie content and enriched with substances useful for the human body may play a role as additional helpers in weight management. In this review, general suggestions for the elaboration of foods with plant-origin functional ingredients for weight management, which help the human body with obesity prevention, based on human clinical trials, are proposed. Including new ingredients of plant-origin for the preparation of traditional foods helps to have a balanced diet and may contribute to weight management and obesity prevention.
Keywords: obesity prevention